Valiant ambition : George Washington, Benedict Arnold, and the fate of the American Revolution - Philbrick, Nathaniel (New York : Viking, 2016)
Presents an account of the middle years of the American Revolution that shares insights into the relationship between George Washington and Benedict Arnold.
Includes bibliographical references (pages 375-403) and index.
Keywords: Washington, George, -- 1732-1799.; Arnold, Benedict, -- 1741-1801.; United States. -- Continental Army -- Biography; Generals -- United States -- Biography; United States -- History -- Revolution, 1775-1783 -- Biography